Cultural Values, Human Development and Women’s Empowerment Towards Better Environmental Performance - Falguera, Fernanda Pereira Sartori [UNESP]; Furlan, Marcelo; Mariano, Enzo Barberio [UNESP] (Springer Nature, 2025)
Human actions depend both on the motivation to act, which can be influenced by national culture, and on the opportunities and choice options people have that enable them to become agents. Using the lenses of the Capability Approach (CA), Feminist Political Ecology (FPE) and Hofstede’s Cultural Values, the objective of this work is to analyze the relationship between cultural values and environmental performance, and the mediating effect of gender inequality and average male and female human development. For this, we applied partial least squares structural equation modeling (SEM) in a sample of 61 countries. Our findings not only reveal that cultural values and male and female human development are important predictors of Environmental Performance, but also unravel how and why they matter. The investment in aspects that strengthen male and female agency is an important path to a better environment, with female human development having a more pronounced effect. Although gender-differentiated, the impact of cultural values is paramount, as is the relative contribution of each dimension of female and male human development. In addition to uniting an agency and value-based aspirational vision towards a better environment, the present research innovates in jointly considering male and female indicators in a cultural analysis that links the CA and the FPE to substantiate its empirical findings. The research sought to offer a more accurate portrait of our societies, in the sense that humans, regardless of gender, will need to accept the duty of preparing a sustainable world for current and future generations.
Keywords: Capabilities; Environmental quality; Gender equality; National culture